A COMMUNITY BASED RANDOMIZED CONTROLLED TRIAL OF IRON AND ZINC SUPPLEMENTATION IN INFANTS: EFFECTS ON GROWTH AND DEVELOPMENT - T. Lind; B. Lonnerdal; H. Stenlund; I. Gamayanti; D. Ismail; R. Seswandhana; L. Persson ("Paediatrician" Publishers LLC, 2006)
Deficiencies of iron and zinc are associated with delayed development, growth faltering, and increased infectious disease morbidity during infancy and childhood. Combined iron and zinc supplementation may therefore be a logical preventive strategy. Objective: the objective of the study was to compare the effects of combined iron and zinc supplementation in infancy with the effects of iron and zinc as single micronutrients on growth, psychomotor development, and incidence of infectious disease. Design: Indonesian infants (n = 680) were randomly assigned to daily supplementation with 10 mg Fe (Fe group), 10 mg Zn (Zn group), 10 mg Fe and 10 mg Zn (Fe + Zn group), or placebo from 6 to 12 mo of age. Anthropometric indexes, developmental indexes (bay ley scales of infant development; sid), and morbidity were recorded. Results: at 12 mo, two factor analysis of variance showed a significant interaction between Iron and Zinc for weight for age z score, knee heel length, and sid psychomotor development. Weight forage z score was higher in the Zn group than in the placebo and Fe + Zn groups, knee heel length was higher in the Zn and Fe groups than in the placebo group, and the sid psychomotor development index was higher in the Fe group than in the placebo group. No significant effect on morbidity was found. Conclusions: single supplementation with zinc significantly improved growth, and single supplementation with iron significantly improved growth and psychomotor development, but combined supplementation with iron and zinc had no significant effect on growth or development. Combined, simultaneous supplementation with iron and zinc to infants cannot be routinely recommended at the iron to zinc ratio used in this study. Key words: infants, growth, knee heel length, development, iron, zinc.